Care Practices Among Healthy Older People in Northeastern Thailand - Onanong Nilphat (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Currently, Thai people are living longer lives than in previous generations. As such, it is worth learning from them how they maintain their health. This ethnographic study aimed to describe care practices of healthy older people in one rural community of Udon Thani province, located in northeastern Thailand. Through purposive sampling and snowball sampling techniques, 15 key informants (9 females) who were 70-87 years old and perceived themselves as being healthy and 11 general informants, including eight family members, two health volunteers, and one elderly club leader were recruited. Data were collected between December 2017 and July 2019. Information about informants’ activities and the cultural context of the community was collected through participant observation. Three focus group interviews were conducted among the key informants. The key informants and general informants participated in in-depth interviews. Thematic analysis was employed for data analysis. Trustworthiness was achieved through triangulation of data collection methods, member checking, and peer debriefing. Within the cultural context of the study of the prosperous community in Isan, care practices of the informants involved three themes: ‘healthiness of older people,’ ‘living in a natural way,’ and ‘living by one’s faith.’ Healthiness of older people was determined by 1) physical strength and self-reliance and 2) peaceful mind and happy life. Living in a natural way which is simple, sufficient, and conventional, without extravagance, constituted the care practices that this group of healthy older people used to achieve and maintain their healthiness. Their natural way of living included: eating local/natural Isan food, performing modest physical activities, living a peaceful life, and using natural/modern remedies. In addition, living by one’s faith, including nature, Buddhist doctrine, as well as ancestors’ spirits and community traditions, was a care practice contributing to healthiness. These findings reflect care practices of healthy older people living in one rural community of northeastern Thailand. Health professionals should be culturally sensitive in promoting health correspondently with a natural way of living and the faith practiced by the community.